1999
DOI: 10.1183/09031936.99.14612669
|View full text |Cite
|
Sign up to set email alerts
|

Arousal in patients with gastro-oesophageal reflux and sleep apnoea

Abstract: Nocturnal gastro-oesophageal reflux has been observed in patients with obstructive sleep apnoea (OSA). Negative intrathoracic pressure during apnoeas and arousal have been suggested as the underlying mechanisms.In order to evaluate this hypothesis, the coincidence and sequence in time of arousal, apnoea and reflux events were analysed. Fifteen patients with OSA or heavy snoring were studied by means of standard polysomnograpy with parallel recording of 24-h oesophageal pH.Reflux events during the day were pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
3
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(94 citation statements)
references
References 12 publications
3
84
3
4
Order By: Relevance
“…However, the authors could not establish a specific linkage between GERD and apnoea events. 3 More recent studies [4][5][6][7][8] showed that OSAS patients frequently manifest GERD, but did not establish a cause-effect relationship. For example, Ing et al 6 determined that OSAS patients manifested more reflux and greater time with an oesophageal pH below 4.0.…”
Section: Introductionmentioning
confidence: 99%
“…However, the authors could not establish a specific linkage between GERD and apnoea events. 3 More recent studies [4][5][6][7][8] showed that OSAS patients frequently manifest GERD, but did not establish a cause-effect relationship. For example, Ing et al 6 determined that OSAS patients manifested more reflux and greater time with an oesophageal pH below 4.0.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 While some studies suggest a temporal relationship between obstructed breathing events and sleep reflux events, 4,12 previous studies have not demonstrated a consistent association. In addition, the number of obstructed breathing events far outweighs the number of sleep reflux events; therefore, there is a high likelihood that these two phenomena may occur by chance.…”
Section: Discussionmentioning
confidence: 97%
“…events in temporal association with an obstructed airway, this relationship is weak at best. 4,7,12 The role of obesity in the link between OSA and GER remains unclear. Obesity is a risk factor common to both OSA and GER and therefore represents a potential mechanism for the link between the two conditions.…”
Section: Mechanism Of Gastroesophageal Reflux In Obstructive Sleep Apmentioning
confidence: 99%
See 1 more Smart Citation
“…T he prevalence of gastroesophageal refl ux disease (GERD) is signifi cantly higher in patients with obstructive sleep apnea (OSA) (1)(2)(3)(4)(5)(6), and 54% to 76% of patients with OSA have GERD (2,3). Th ese two conditions share one common risk factor, namely obesity, which increases the risk for both apnea and refl ux (7).…”
mentioning
confidence: 99%